Readiness of health facilities to deliver family planning services and associated factors in urban east-central Uganda - Jacquellyn Nambi Ssanyu; Rornald Muhumuza Kananura; Leif Eriksson; Peter Waiswa; Mats Målqvist; Joan Nakayaga Kalyango (Reproductive Health)
Abstract Background Health facility readiness is essential for realizing voluntary, rights-based family planning. However, many countries, including rapidly urbanizing Uganda, face challenges in ensuring their health facilities are sufficiently equipped to meet the growing demand for these services. This study assessed readiness and associated factors across public, private-not-for-profit (PNFP), and private-for-profit (PFP) health facilities in urban east-central Uganda to guide strategies for improving service delivery. Methods The study used secondary data from a cross-sectional study done in Jinja City and Iganga Municipality, including a health facility assessment and health worker survey. Readiness was measured using the Service Availability and Readiness Assessment methodology, and health worker knowledge and biases were assessed through the Situation Analysis approach. Sample weights adjusted for facility and health worker representation, and linear regression examined associations between readiness scores and various factors. Results Among 152 health facilities, 94.2% offered family planning services, with an average readiness score of 46.7% (standard deviation ± 17.0). Short-acting methods had high availability (99.0%), while long-acting reversible contraceptives (34.2%) and permanent options (8.9%) were less available, compounded by prevalent stock-outs. Additionally, staff refresher training was inadequate, particularly in PFP facilities (50.4%), and health worker knowledge, confidence and willingness to provide some methods, particularly long-acting options and natural family planning counselling, were low. Notably, out of 261 health workers, 97.7% imposed at least one restriction to service access based on either age, parity, marital status, or spousal consent, more pronounced in PNFP facilities. Readiness was significantly associated with facility level (health centre level II facilities: β = -9.42, p = 0.036; drug shops: β = -11.00, p = 0.022), external supervision (β = 9.04, p = 0.009), holding administrative meetings (β = 9.72, p = 0.017), and imposing marital status (β = -9.42, p = 0.017) and spousal consent access barriers (β = 6.24, p = 0.023). Conclusions This study found sub-optimal facility readiness, highlighting the need to strengthen governance of services across both public and private sectors, implement comprehensive training for health workers in both sectors, and align policies to ensure equitable access to a full range of services for all clients.